Mobile Learning in Botswana’s Secondary Schools: Investigating Teacher Readiness and Institutional Barriers - Mafa, Rodnie Kgalemelo; Govender, Desmond Wesley; Moepswa, Tirelo Modise (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This study examined the readiness of teachers in Botswana’s secondary schools to integrate mobile technology, specifically smartphones, into their teaching practices. While smartphones have become pervasive in students’ daily lives and offer significant opportunities to enhance educational experiences, many educators face challenges in utilizing these tools effectively within the classroom context. The study employed a mixed-methods approach involving 50 secondary school teachers and found that 70% of teachers reported low confidence in using mobile technology for teaching, with 80% indicating they had not received sufficient training. Additionally, 60% of teachers identified classroom distractions as a major challenge, while 50% cited inadequate infrastructure, including unreliable internet access and a lack of technical support. Despite these barriers, 90% of teachers expressed a strong interest in professional development programs focused on mobile learning. The study concluded by recommending targeted teacher training initiatives, improvements in school infrastructure, and the development of policies to support the effective integration of mobile technology in secondary education.